Transformasi Pangan Lokal Menjadi Produk Bernilai Ekonomi di Desa Ngrogung Kecamatan Ngebel Ponorogo - Muhammad Ainur Rofiqi; Nafi'ah (Social Science Academic, 2025)
Innovation in the use of local food ingredients is a strategic effort to support food independence while increasing the economic competitiveness of rural communities. This research developed a new product in the form of jackfruit cake as an alternative processed food with higher economic value, longer shelf life, and the potential to become a typical souvenir of Ngrogung Village, Ngebel District, Ponorogo Regency. This community service program uses the Asset Based Community Development (ABCD) method introduced by John McKnight and Jody Kretzmann. This asset-based approach encourages the community to explore internal potential and directs changes in accordance with the community's vision. The activity was carried out through a collaboration between the Community Service Lecture (KPM) group and the UPT BLK Karanglo Lor Ponorogo. The training results showed an increase in knowledge, skills, and socio-economic impacts on the community, especially in processing local food into value-added products. Thus, the jackfruit cake innovation can be a model for sustainable community empowerment based on local potential.